PIMCO stress test on Cyprus Banking System: a critical review four years later - Solomonides, Constantinos (Τμήμα Εμπορίου, Χρηματοοικονομικών και Ναυτιλίας, Σχολή Διοίκησης και Οικονομίας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2017)
The Cypriot Government requested an Economic Adjustment Programme (bail-out) from the European Financial Stability Facility on 25 June 2012, citing difficulties in supporting its banking sector from the exposure to the Greek debt. Thus, at the request of TROICA, PIMCO was appointed during October 2012 to quantify the capital requirements of the Cypriot Banks in order to finalise the Adjustment Programme. A Steering Committee was appointed for monitoring and supervising the process of the preparation of the report and provided a set of macroeconomic factors to assist in the forecasting. Further assumptions and methodologies were used in the exercise. The due diligence results played a major role in the future financial decisions for the Cypriot Banking system and the size and format of the Economic Adjustment Programme for Cyprus, with the pick of the iceberg being the haircut that followed on March 2013, a first time ever bail–in approach to be implemented in the EU. The purpose of the paper is to evaluate the PIMCO report based on a number of reviews published in the meantime and examine its economic forecasts and methodologies four years after the bail-in. The report findings align with numerous publications supporting that due to PIMCOs overestimation of the Banks’s needs Cyprus was led to a much bigger Adjustment programme than was actually necessary, and perhaps the bail-in programme had become inevitable.
Keywords: Cyprus; Banking crisis; PIMCO report; Bail-in